1998
DOI: 10.1164/ajrccm.157.2.9705046
|View full text |Cite
|
Sign up to set email alerts
|

Respective and Combined Effects of Prone Position and Inhaled Nitric Oxide in Patients with Acute Respiratory Distress Syndrome

Abstract: Inhaled nitric oxide (NO) and prone position (PP) are two of the new therapeutics proposed in the setting of acute respiratory distress syndrome (ARDS). The aim of this study was to evaluate the hemodynamic and respiratory effects of NO and prone position in patients with ARDS. Fourteen patients, sedated, paralyzed, and ventilated using volume-control mode, were prospectively investigated. All patients had a radial artery catheter, a pulmonary artery catheter, and a 3-F fiberoptic thermistor catheter advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 19 publications
4
35
1
4
Order By: Relevance
“…Recently, several studies have investigated the effects of NO and prone positioning in patients with ARDS and have found a comparable improvement or a greater effect on oxygenation of prone positioning compared to NO [39][40][41][42]. However, most studies found an additive benefit when the two treatment modalities were combined [39][40][41]. Optimisation of alveolar recruitment increases delivery of NO to target cells, thereby improving the response to NO.…”
Section: Nitric Oxide and Almitrinementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have investigated the effects of NO and prone positioning in patients with ARDS and have found a comparable improvement or a greater effect on oxygenation of prone positioning compared to NO [39][40][41][42]. However, most studies found an additive benefit when the two treatment modalities were combined [39][40][41]. Optimisation of alveolar recruitment increases delivery of NO to target cells, thereby improving the response to NO.…”
Section: Nitric Oxide and Almitrinementioning
confidence: 99%
“…The majority of the studies (63%) did not describe the support used for pronation [26,27,39,40,42,43,[51][52][53][54][55][57][58][59][60][61]. Thus, 20% did not release the abdomen [23,56], whilst 80% attempted to ensure free abdominal movements [4,5,18,22,24,25,28,41,50,62,63].…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…This value was chosen on the basis of the literature, in which other authors have used changes of 10 to 20% in this ratio, or an absolute improvement of 20 mmHg in PaO 2 , to define which patients were responders to PP. 6,7,17,23,27 Using this figure of 15%, most of our patients (78.0%) did improve their oxygenation in PP as early as 30 minutes after the maneuver (65.85% of all patients). Moreover, 62.5% had a continuing response even after changing back to SP.…”
Section: Discussionmentioning
confidence: 75%
“…Com relação aos parâmetros ventilatórios utilizados nos três momentos da pesquisa (Pinsp, f, FiO 2 , Vt, e Ve), não foram observadas modificações significativas em nenhuma das fases propostas. Porém, ao relacioná-los isoladamente notou-se que: quanto maior o valor da PEEP e menor volume-corrente, complacência estáti-ca, pH, PaO 2 , e SaO 2 maior a mortalidade 15,22,34,[35][36][37][38][39][40][41][42][43][44] . Optou-se em realizar o protocolo iniciando na posição supina, pela facilidade de todos os pacientes estarem nesta posição, no entanto se tivessem sido aleatorizados e alguns iniciassem o estudo na posição prona, talvez os resultados pudessem ser diferentes do exposto pela diminuição do efeito carry-over ou de evolução temporal da doença.…”
Section: Discussionunclassified